2019-2029 Uganda National Bamboo Strategy and Action Plan: National plans and policies - Ministry of Water and Environment, Uganda (International Bamboo and Rattan Organisation (INBAR), 2020)
This report was commissioned, developed and written by the Ministry of Water and Environment of Uganda. It was produced by INBAR as part of its series on national bamboo plans and policies.